Estimated pulse wave velocity can predict the incidence of new-onset atrial fibrillation: A 11-year prospective study in a Chinese population - Chen, Haojia; Chen, Guanzhi; Zhang, Liling; Wu, Weiqiang; Li, Weijian; Wang, Xianxuan; Yan, Xiuzhu; Chen, Youren; Wu, Shouling (Frontiers in Cardiovascular Medicine, 2022)
Background Arterial stiffness, a risk factor for atrial fibrillation (AF), is rarely applied in clinical practice because of the difficulty and high cost of its measurement. Estimated pulse wave velocity (ePWV) is a simple, reproducible, and non-invasive index of arterial stiffness. This study was to assess the predictive value of ePWV for the risk of new-onset AF. Methods Subjects were selected from the Kailuan cohort study population who underwent initial physical examination between 2006 and 2008. A total of 96,561 subjects were ultimately included in the final analysis. ePWV was divided into four groups according to quartiles. The Kaplan–Meier method was used to calculate the cumulative incidence of AF. A Cox regression model was used to assess the predictive value of estimated arterial stiffness for new-onset AF. Results Mean age of subjects was 51.47 ± 9.68 years, while 76,968 (79.65%) were male and 19,663 (20.35%) were female. During mean follow-up period of 11.77 years, 1,215 AF events occurred. Results of the Kaplan–Meier analysis showed that the incidence of new-onset AF increased with increase in ePWV. Cox regression analysis showed that in the total population, the incidence of new-onset AF was 1.64, 1.90, and 2.64 times higher in the medium, medium-high, and high ePWV groups, respectively, compared with the low ePWV group. When stratified according to sex, ePWV had higher predictive value in the female population. Conclusions Increased ePWV increases the incidence of new-onset AF, and may promote application of more aggressive primary prevention. Trial registry name Risk factors and intervention for cardiology, cerebrovascular and related disease (Kailuan Study); URL: http://www.chictr.org.cn/showproj.aspx?proj=8050; Registration number: ChiCTR-TNRC-11001489.